2022
DOI: 10.3389/fnut.2022.965376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, trend, and predictor analyses of vitamin D deficiency in the US population, 2001–2018

Abstract: BackgroundThe National Health and Nutrition Examination Surveys (NHANES) collect and release data to the public every 2 years. The latest NHANES study on the vitamin D status of Americans was based on data from 2001 to 2014, and the latest data (2015–2016 and 2017–2018) have not been studied yet. Thus, we extracted all the available data from NHANES (2001–2018), aiming to analyze the prevalence and trends of vitamin D deficiency (VDD) in the US population to bridge the research gap.MethodsAccording to previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…Limitations of this study included the relatively low number of participants reported to exhibit excessive scarring, which was identified based on electronic medical records and included patients with a diagnosis of keloid or hypertrophic scarring, and the fact that most of the participants reported White ethnicity, which may make the findings less generalisable to other ethnic groups that display elevated risks for excessive scar formation 95 . Additionally, the rates of vitamin D deficiency in both the excessive scarring group and the unaffected control group (5.1% and 2.4%, respectively) were much lower than rates of vitamin D deficiency in the United States (24.6% for the years 2001–2018), 98 which has a more ethnically diverse population.…”
Section: Keloids: More Than Just ‘Scars’mentioning
confidence: 89%
“…Limitations of this study included the relatively low number of participants reported to exhibit excessive scarring, which was identified based on electronic medical records and included patients with a diagnosis of keloid or hypertrophic scarring, and the fact that most of the participants reported White ethnicity, which may make the findings less generalisable to other ethnic groups that display elevated risks for excessive scar formation 95 . Additionally, the rates of vitamin D deficiency in both the excessive scarring group and the unaffected control group (5.1% and 2.4%, respectively) were much lower than rates of vitamin D deficiency in the United States (24.6% for the years 2001–2018), 98 which has a more ethnically diverse population.…”
Section: Keloids: More Than Just ‘Scars’mentioning
confidence: 89%
“…Vitamin D deficiency has become a global issue, especially for individuals whose occupation or lifestyle precludes them from gaining sufficient sun exposure. 21 Vitamin D is a crucial nutrient in maintaining bone quality via maintenance of calcium and phosphorus balance. In spine surgery, older age is a risk factor for decreased bone mineral density leading to osteoporosis and increased risk of degenerative spine disorders.…”
Section: Vitamin Dmentioning
confidence: 99%
“…10,22 Vitamin D deficiency is defined by the Endocrine Society for Clinical Practice Guideline as a serum concentration <50 nmol/L, whereas a concentration >75 nmol/L is sufficient. 21,23,24 The vitamin D metabolite total 25-hydroxyvitamin D is the most commonly used biomarker in determining serum levels. 25 The goal concentration of serum vitamin D is around 75 nmol/L, but modifications accounting for differences in age, weight, and ethnicity are needed.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Estimates of the prevalence of VDD ranges from 24% (United States) to 40% (European Union) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. It is now evident that, in addition to the musculoskeletal system, most tissues and cell types express VitD receptors and VitD, in addition to its role in promoting and maintaining skeletal health, confers complex health benefits in multiple organ systems, including the immune system and the cardiovascular system [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%